Peran Pendidikan Agama Islam dalam Membentuk Karakter Jujur pada Anak Usia Dini - Hana Giri Tri Lathifah; Keisya Putri Ayu Rahmadini; Muhammad Dafid Hermawan; Faris Rasyid; Abdul Fadhil (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This article was created to examine the role of Islamic religious education in forming honest character in early childhood, where when children are still at the age known as the golden age, they tend to learn a lot from what they see and experience. It contains the role of Islam in becoming a forum for instilling and teaching honest character to young children through fun methods by implementing honesty from the holy book Al-Qur'an, hadith, and exemplary stories of the Prophets and Apostles of that era. A long time ago. Later, honest character education through the role of the Islamic religion will influence their character in the future, and what their character, behavior and mindset will be like in the future.